2014
DOI: 10.1155/2014/632986
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Electron Transfer Chain Induced by Acute Carnosine Administration in Skeletal Muscle of Young Rats

Abstract: Serum carnosinase deficiency is an inherited disorder that leads to an accumulation of carnosine in the brain tissue, cerebrospinal fluid, skeletal muscle, and other tissues of affected patients. Considering that high levels of carnosine are associated with neurological dysfunction and that the pathophysiological mechanisms involved in serum carnosinase deficiency remain poorly understood, we investigated the in vivo effects of carnosine on bioenergetics parameters, namely, respiratory chain complexes (I–III, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…These data also suggest that TFAM increased the aspartate-malate shuttle to increase NAD + import into the mitochondrial matrix. Carnosine, an inhibitor of electron transport chain (ETC) in animals (21), was also lower in Tg mice compared with Wt mice in both the chow and HFD groups (Fig. 2V).…”
Section: Tfam Enhances Skeletal Muscle Energy Metabolismmentioning
confidence: 96%
“…These data also suggest that TFAM increased the aspartate-malate shuttle to increase NAD + import into the mitochondrial matrix. Carnosine, an inhibitor of electron transport chain (ETC) in animals (21), was also lower in Tg mice compared with Wt mice in both the chow and HFD groups (Fig. 2V).…”
Section: Tfam Enhances Skeletal Muscle Energy Metabolismmentioning
confidence: 96%
“…A literature report showed that rats receiving carnosine acutely presented reduced activity of complexes I-III and II, as well as a trend of decrease in complexes II and III activities in skeletal muscle. 31 However, in cerebral cortex tissue of rats, acute carnosine treatment enhanced the activities of complexes I-III and II-III. 30 It has been shown that in the yeast Saccharomyces cerevisiae , carnosine produced contrasting effects on growth and viability, which suggested to be related to the organism’s energy metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, carnosine levels in the human skeletal muscle [113], as well as the homocarnosine concentration in human CSF [114] significantly decrease with age. A recent paper published by Macarini and co-workers [115] corroborates such proposition. It was showed a significant decrease in the mitochondrial respiratory chain complexes I-III and II activities in skeletal muscle of young rats (30 days old) receiving carnosine (100 mg/kg body weight) acutely, as compared to animals receiving vehicle.…”
Section: Id In Scdmentioning
confidence: 66%